PARTISIPASI MASYARAKAT DALAM MUSYAWARAH PERENCANAAN PEMBANGUNAN DI KELURAHAN JEBRES - Qomaruddin, Heriwanto Panjaitan (Transformasi, 2015)
Participation is the act of participating mentally and emotionally of person group situation whichencourages responbility in them and Participatory Village Development Planning Meeting(PVDM ) basically is a village development planning forum particularly designed as one of theinstruments used to accommodate society's needs in the development programs. With this forum,all of the development programs are directed to be able to cope with the real problems faced bythe society so that the development results can significantly contribute to the increasing of theirwelfare as PVDM reflecting people’s participation. The aim of this research was to understandthe of people’s participation in development planning meeting at Jebres village Surakarta, bydescriptive qualitative methods. The results of research shows that the development Planningmeeting is still far from the basic ideas of participatory development planning, likely more formalthan substantial.Key words : Participation, Planning, Development